EPIDEMIOLOGIChESKOE ISSLEDOVANIE RASPROSTRANENNOSTI OSTEOARTROZA SREDI KORENNYKh SEL'SKIKh ZhITELEY RESPUBLIKI SAKhA (YaKUTIYa). SOOBShchENIE 2 - R. N. Protopopova; Sh Erdes; V. G. Krivoshapkin (Научно-практическая ревматология, 2000)
Aim: Study of osteoarthrosis epidemiology in native populations of the North rural areas. Material and methods: Study was carried out by complete epidemiologic examination among grown up native populations of the Republic of Saha (Yakutia) - yakuts and evenks in total number of 1216 persons. To put the diagnosis of osteoarthrosis the criteria developed at the Institute of Rheumatology of RAMS were used. Results: Osteoarthrosis prevalence in the examined sample was 18.0% including 9.4%) as definite and 8.6% as possible. Prevalence of the disease among males was practically twice lower than in females (12.6%) and 22.5% correspondingly, p<0.01). Definite correlation between the prevalence of osteoarthrosis and age was found. It was demonstrated that generalized form of the disease prevailed, and its quote was practically 74%> of cases and prevalent localizations except knee and wrist joints were elbow and shoulder joints.